Proteasomal and lysosomal protein degradation and heart disease - Wang, Xuejun; Robbins, Jeffrey (Journal of molecular and cellular cardiology, 2014)
In the cell, the proteasome and lysosomes represent the most important proteolytic machineries, responsible for the protein degradation in the ubiquitin–proteasome system (UPS) and autophagy, respectively. Both the UPS and autophagy are essential to protein quality and quantity control. Alterations in cardiac proteasomal and lysosomal degradation are remarkably associated with most heart disease in humans and are implicated in the pathogenesis of congestive heart failure. Studies carried out in animal models and in cell culture have begun to establish both sufficiency and, in some cases, the necessity of proteasomal functional insufficiency or lysosomal insufficiency as a major pathogenic factor in the heart. This review article highlights some recent advances in the research into proteasome and lysosome protein degradation in relation to cardiac pathology and examines the emerging evidence for enhancing degradative capacities of the proteasome and/or lysosome as a new therapeutic strategy for heart disease. This article is part of a Special Issue entitled “Protein Quality Control, the Ubiquitin Proteasome System, and Autophagy”. •The proteasome and lysosomes are the main proteolytic machineries in the cell.•Cardiac proteasome functional insufficiency is a major pathogenic factor.•Enhancement of proteasome function protects against proteotoxicity.•Lysosomal insufficiency might be involved in common cardiac pathogenesis.•Promoting proteasomal or lysosomal function may be of therapeutic benefits.